Experimental and computational analysis of the in situ tensile deformation of 2D honeycomb lattice structures in Ni single crystals. (1st April 2020) - Xu, Alan; Saleh, Michael; Bhattacharyya, Dhriti
Abstract: A ~12 μm thick film of single crystal Ni was shaped with a focused ion beam (FIB) instrument to form a set of tensile samples with hexagonal holes of sides ~3 μm long and ~2.5 μm thick arranged in a honeycomb lattice structure. The plane normal of the film was <001> and the tensile axis was parallel to <100>. The samples were then tested in tension in situ inside a scanning electron microscope. The tensile properties, viz., yield strength and peak strength observed in the lattice sample, were higher than those of a standard sample by about 30%, while the strain to fracture decreased drastically. Finite element (FE) modelling, utilising size effect corrections and the modified Gurson model, was performed to elucidate the response of the microlattice, and it was found that the changes in the mechanical properties could be explained by the stress distribution around the hexagonal holes and localised sample size effects. These models were corroborated by observations of the crystal orientation using electron backscatter diffraction (EBSD) maps. The assumption of void formation as a mechanism of failure in the Gurson model was validated experimentally by transmission electron microscopy, which showed nano-voids in the thin bands formed by localised slip.